2015
DOI: 10.1016/j.ram.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Efecto antifúngico de extractos fenólicos y de carotenoides de chiltepín (Capsicum annum var. glabriusculum) en Alternaria alternata y Fusarium oxysporum

Abstract: The effect of phenolic and carotenoid extracts from chiltepin fruits on mycelial growth and the inhibition of conidial germination of Alternaria alternata and Fusarium oxysporum were investigated in the present work. Phenolic extracts inhibited mycelial growth of A.alternata by 38.46%, and significantly reduced conidial germination on the fifth day after treatment to 92% in relation to control. No significant changes were observed in the inhibition of mycelial growth in Fusarium oxysporum; however, the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
1
9
0
3
Order By: Relevance
“…In this study, it was observed that the tested phenolic compounds exert a cytotoxic activity in vitro against F. proliferatum (AACC0215) and this activity increase when they are complexed with CSNPs. These results are in line with other studies in which phenols extract from olive leaves show an antifungal activity (Markin et al, 2003;Steinkellner and Mammerler, 2007;Goldsmith et al, 2015;Rodriguez-Maturino et al, 2015;Zorić et al, 2016). As reported by Ansari et al (2013) the phenols antimicrobial activity could be due to a synergistic action of the antioxidant and chelating power of the hydroxyl groups of the phenolic ring that form hydrogen bonds with cell wall proteins of microorganisms.…”
Section: In Vitro Inhibition To Growthsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, it was observed that the tested phenolic compounds exert a cytotoxic activity in vitro against F. proliferatum (AACC0215) and this activity increase when they are complexed with CSNPs. These results are in line with other studies in which phenols extract from olive leaves show an antifungal activity (Markin et al, 2003;Steinkellner and Mammerler, 2007;Goldsmith et al, 2015;Rodriguez-Maturino et al, 2015;Zorić et al, 2016). As reported by Ansari et al (2013) the phenols antimicrobial activity could be due to a synergistic action of the antioxidant and chelating power of the hydroxyl groups of the phenolic ring that form hydrogen bonds with cell wall proteins of microorganisms.…”
Section: In Vitro Inhibition To Growthsupporting
confidence: 91%
“…The control of these fungi, responsible for pre-and post-harvested diseases of agricultural products, is an issue that remains unresolved, along with the excessive environmental impacts of chemicals to tackle this problem. Current efforts are focused to search new strategies and effective alternatives for microbial control and to reduce the excessive use of synthetic fungicides which negatively impact the environment and human and animal health (Cota-Arriola et al, 2013;Rodriguez-Maturino et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Es importante considerar las propiedades químicas de los disolventes empleados, ya que la polaridad influye en el tipo de compuesto y la capacidad de extracción, así como la eficiencia de los compuestos frente a radicales libres (Bae et al, 2012;Rodríguez-Maturino et al, 2015). Lo anterior concuerda con los resultados obtenidos, debido que al disminuir la concentración de etanol y emplear solo agua, aumenta la polaridad.…”
Section: Resultados Y Discusiónunclassified
“…El incremento de compuestos fenólicos en el tejido foliar de plantas de algodón tratadas con T. longibrachiatum cepa ICA-4, podría tener un efecto bioprotector contra fitopatógenos del suelo. Rodríguez-Maturino et al (2015), sugieren que el incremento de compuestos fenólicos podría interactuar con la pared celular de los hongos fitopatógenos inhibiendo algunas enzimas fúngicas, afectando el crecimiento del micelio y disminuyendo la severidad de la enfermedad. El incremento de la enzima POX en el tejido foliar de plantas inoculadas Tabla 1.…”
Section: Resultados Y Discusiónunclassified